Validation of a TAM Technology Acceptance Model in Dominican University Students - Emmanuel Silvestre; Alexander Montes Miranda; Vladimir Figueroa Gutiérrez (Pontificia Universidad Católica del Perú, 2022)
In the context of the virtualization of university education due to the Covid-19 pandemic, we conducted a study to establish the determinants of the intention to use the virtual classroom, following a theoretical model based on the Technology Acceptance Model modified by Park (2009) and including the factors Attitude, Perceived Usefulness, Perceived Ease, Virtual Self-Efficacy, Subjective Norm and Accessibility of the system. The sample consisted of 1260 self-selected students from 13 Dominican universities. To check the validity and reliability of the measurement instrument, we performed a Confirmatory Factor Analysis, which determined that the System Accessibility factor had to be eliminated because it was based on a single item that did not have discriminatory validity. One item was eliminated from the Subjective Norm factor to bring it to an acceptable reliability. In general, the validity of the instrument was sustained, but its fit indices with the theoretical model could be improved. With the Multiple Mediation Analysis, we were able to verify that the Subjective Norm, the social factor, was the factor with the most significant statistical influence on the Intention to Use the virtual classroom, both directly and indirectly. Indirectly, the Subjective Norm was mediated by Perceived Usefulness and Attitude. The other factor that had a significant influence, both directly and indirectly, on Intention to Use was Virtual Self-efficacy. Indirectly, this Self-efficacy was mediated by Perceived Ease, Perceived Usefulness and Attitude.